PET/CT in Cancer of Unknown Primary - Seshadri, Nagabhushan; Eswar, Chinnamani (Springer International Publishing : Imprint: Springer, 2017)
This pocket book offers a rapid and concise overview of the utility of PET/CT in the management of patients with cancer of unknown primary (CUP). Readers will gain an appreciation of the unique information provided by PET/CT on the molecular and metabolic changes associated with CUP, which can occur in the absence of corresponding anatomical alterations. Characteristic imaging appearances are documented with the aid of a series of teaching cases that serve to illustrate the potential improvements in patient management that may be achieved through early use of PET/CT in the diagnostic pathway. In addition, the relation of the clinical and pathological background to imaging is explained. The book is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging (compiled under the auspices of the British Nuclear Medicine Society) and will be an excellent asset for all clinicians, nuclear medicine physicians, radiologists, radiographers, and nurses who routinely work in multidisciplinary teams involved in the management of these patients.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books